The use of a call program to enhance the language performance of low proficiency learners / P Kangathevi a/p Ponnudorai - Ponnudorai, P Kangathevi (2015)
The purpose of this study was to investigate the use of a computer assisted language learning (ELLIS) program to enhance the language performance of low proficiency learners. Additionally, this study aimed to identify the causes for the disparity if there was any between the scores obtained for the ELLIS program and the final assessment. The sample population consisted of forty diploma nursing students who had to follow the Basic English subject at Masterskill University College of Health Sciences (MUCH). The participants selected their own mode of delivery i.e. CALL (ELLIS) or face-to-face (F2F). Pre-test, post-test, a pre-study questionnaire and an ELLIS course experience questionnaire (E-CEQ) were the instruments for the study. The data were subjected to analysis through descriptive statistics, t-test, and thematic analysis. The results for the reading comprehension, grammar, vocabulary, speaking and listening components indicated that the differences between the two groups in their post-test scores were statistically significant favouring the F2F classroom learning mode. This means that the F2F control group outperformed the CALL (ELLIS) group rendering the CALL (ELLIS) remains as a tool to learn, F2F proved to be more effective in enhancing the performance of low proficiency learners’. For the potential causes for the less effectiveness of the CALL (ELLIS) program, the study found that, the lack of interaction faced by learners between various aspects such as an instructor as well as non-human aspects was identified. Apart from that, there is also a lack of interaction in the CALL learning environment. In addition, the study also found that students’ computer competency level and their preference were not factors that influenced the language performance results. Thus, the findings of this study prompted the University College academic board to revise the Basic English course. Instead of CALL (ELLIS) only, the University College look up the suggestion given that is a blend of CALL (ELLIS) program and F2F classroom learning instructed by a teacher to enhance the low proficiency students’ language performance.